Efektivitas E-Modul Pada Materi Sistem Koloid Berbasis Discovery Learning Terhadap Hasil Belajar SMA/MA - Dewi Rika Aryani; Desy Kurniawati (Universitas Negeri Padang, 2022)
The 2013 curriculum implemented by the government is expected to improve the quality of education. The scientific approach is the approach used in K13, which is a science-based approach. The research carried out is a follow-up study of the development of discovery learning-based colloid system e-modules for high school/MA students which has been tested for validity and practicality, but its effectiveness has not been tested. The purpose of this experiment is to see the effectiveness of using discovery learning e-modules for high school/MA students. The type of research used is pre-experimental using One Group-Pretest-Postest. The results obtained from this study are t-test with a significance level of 0.05, namely sig(2-Tailed) data obtained 0.000 proving that H0 is rejected, because the value of Sig <0.05 and H1 is accepted. The result of the N-Gain value in the sample class is 0.816. Based on the results of this study, it shows that the application of this e-module is very good in achieving goals and can develop learning outcomes for high school students